Analysis of fluid flow patterns in cylindrical vessels of anaerobic digester using CFD - Muhammad Shakaib,; Najib, Antash; ul Haque, M. Ehtesham (Penerbit Universiti Kebangsaan Malaysia, 2019)
The production of energy from biomass and waste material is gaining popularity worldwide due to the expected depletion of fossil fuels shortly. A device commonly used is anaerobic digester in which microorganisms react with biomass/biodegradable in a vessel and produce useful gases. The performance of anaerobic digester depends on mixing or proper contact of bio-matter with microorganisms. In this paper, flow behaviour is studied in cylindrical vessels of anaerobic digester using Computational Fluid Dynamics (CFD) technique. The study includes simulations for various cylinder dimensions obtained by changing the height and diameter of the digester vessel and locations for fluid inlet and outlet. The results are shown in qualitative terms using velocity profiles and quantitatively in terms of volume of the stagnant zone. The comparison of several geometries at a constant velocity indicates the considerable effect of cylinder aspect ratio (height to diameter ratio) and positions and numbers of inlet and outlet ports on mixing performance. The influence of inlet velocity/Reynolds number is also examined for a few cases. The digester which has an inlet and two outlets on the curved surface (both on the same side) is found to be most suitable. The volume of the dead zone in this configuration at various Reynolds number is less than 30% (based on 0.5% criterion).